2017
DOI: 10.1093/sleep/zsx062
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury Chronically Impairs Sleep- and Wake-Dependent Emotional Processing

Abstract: Study Objectives: A single traumatic brain injury (TBI), even when mild (ie, concussion), can cause lasting consequences. Individuals with a history of chronic (>1-year prior) mild TBI have an increased risk of mood disturbances (eg, depression, suicide). This population also has lingering sleep alterations, including poor sleep quality and changes in sleep stage proportions. Given these sleep deficits, we aimed to test whether sleep-dependent emotional memory consolidation is reduced in this population. We ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 77 publications
(94 reference statements)
2
19
0
Order By: Relevance
“…In light of the frequent occurrence and adverse consequences of sleep disturbances in mTBI, investigators have sought to identify a causal link between sleep and mood outcomes. Mantua and colleagues 71 conducted a study to examine sleep-dependent emotional processing among individuals with chronic mTBI (n = 40) and controls (n = 41). Participants viewed negative and neutral images both before and after a 12-h period including or not including sleep, and memory recognition was assessed at session two.…”
Section: Wickwire Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the frequent occurrence and adverse consequences of sleep disturbances in mTBI, investigators have sought to identify a causal link between sleep and mood outcomes. Mantua and colleagues 71 conducted a study to examine sleep-dependent emotional processing among individuals with chronic mTBI (n = 40) and controls (n = 41). Participants viewed negative and neutral images both before and after a 12-h period including or not including sleep, and memory recognition was assessed at session two.…”
Section: Wickwire Et Almentioning
confidence: 99%
“…These results suggest sleep and wake-dependent emotional processing might underlie poor emotional outcomes associated with chronic mTBI. 71 Sleep Disorders in mTBI Sleep pathologies are described in terms of insufficient sleep quantity, altered sleep architecture, clinical sleep disorders, and circadian misalignment. Sleep and circadian disturbances are associated with numerous and potentially severe daytime consequences.…”
Section: Wickwire Et Almentioning
confidence: 99%
“…Sleep alterations are also present in this population, which may further exacerbate emotional symptoms. Patients with mTBI have less rapid eye movement (REM), longer REM latency, and more sleep complaints [ 25 ]. Taken in context with sleep quality and quantity having a significant influence on the development and persistence of pain, mood, and movement disorders, these findings not only highlight an important consequence of mTBI but also suggest that disorders of sleep, pain, mood, and movement may have shared mechanisms and exponential effects in patients with mTBI.…”
Section: Consequences Of Mild Tbimentioning
confidence: 99%
“…Fluoride accumulation is shown to calcify bones and interestingly the pineal gland ( 63 , 64 ). The clinical relevance of calcified pineal gland has not been fully elucidated; however, it poses an interesting question given the pineal gland’s role in sleep regulation regarding a potential correlation because sleep disruption is a characteristic symptom associated with many neurodegenerative diseases, as well as acute brain trauma ( 65 67 ). More research seems indicated.…”
Section: Discussionmentioning
confidence: 99%